Development of single mode fiber coupling coefficient using kinetic model - Phattaraworamet, T.; Saktioto, T.; Ali, J.; Fadhali, M.; Yupapin, P. P.; Zainal, J.; Mitatha, S. (My University, 2010)
We propose a simple kinetic model that can be used to improve the coupling coefficient value of a single mode fiber coupler in the fabrication process. The proposed model is time independent, where the internal and external parametric functions are included. The simulation is integrated over the coupling ratio range for the various fiber separations. The coupling coefficient value of the device is examined by using the coupling ratio range from 1% to 75%. The result obtained is compared with the experimental results, where it is noted that the separation of fiber cores significantly affects the coupling coefficient, exhibiting exponential behavior. We also found that the coupling coefficient gradient is significantly changed with respect to the coupling ratio. This model can be used to determine power losses of the fiber coupler at the coupled region, while the fabrication of the fiber coupler is operated. © 2009 Elsevier GmbH.
Keywords: Coupling coefficient; Fiber coupler; Kinetic model; Single mode fiber